2020
DOI: 10.1183/23120541.00181-2020
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific and age-related seasonal variations regarding incidence and in-hospital mortality of pulmonary embolism in Germany

Abstract: BackgroundStudies have reported seasonal variations regarding the incidence and the short-term mortality of pulmonary embolism (PE). The aim of this study was to identify sex-specific and age-related differences in seasonal patterns regarding hospitalisations and mortality of PE patients.MethodsWe analysed the impact of seasons on incidence and in-hospital mortality of male and female hospitalised PE patients in Germany (2005–2015) based on the German nationwide inpatient sample.ResultsThe German nationwide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Gender and age significantly differed between the nonsurvivors and survivors groups in ICU hospitalization in our study as reported by Keller et al 24 However, the reason for the disparity remains unclear. Nevertheless, older patients are prone to a series of basic diseases.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Gender and age significantly differed between the nonsurvivors and survivors groups in ICU hospitalization in our study as reported by Keller et al 24 However, the reason for the disparity remains unclear. Nevertheless, older patients are prone to a series of basic diseases.…”
Section: Discussionsupporting
confidence: 70%
“…Compared with the survivors group, the non-survivors group had significantly higher respiratory rate (21.3 [18.1-24.7] vs 19.7 [17.3-22.3], P < 0 .001), lower SBP (110.1 [101.2-122.3] vs 118.4 [108.3-129.4], P < 0.001) and lower SpO2 (96.7 [94.6-98.3] vs 97.0 [95.7-98.5], P ¼ 0.048). Moreover the nonsurvivors group had significantly higher SAPSII (47 36-60 vs 30,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] P < 0.001), SIRS (3 3-4 vs 3, 2-4 P < 0.001), SOFA (5 3-8 vs 3, 1-5 P ¼ 0.006) and APSIII (54 40-75 vs 36, 28-48 P < 0.001) than the survivors group. Similarly, when compared to the survivors group, the non-survivors group had significantly higher creatinine (1.2 [0.8-2.0] vs 0.8 [0.7 -1.1], P < 0.001), blood urea nitrogen (BUN) (30.8 [19.0-46.5] vs 16.1[11.8-22.8], P < 0.5-11.7], P ¼ 0.004).…”
mentioning
confidence: 94%
“…SPE-related mortality was observed in 4.6 % of all SPE cases and 8 % following a meta-analysis of the observational studies. Studies on PE in general from Germany, Japan, Italy, and the USA reported mortality rates of 17 %, 14 %, 10 %, and 12 % respectively [34][35][36][37]. In a recent study on acute PE by the authors of this review, a low PE-related mortality rate of 3.4 % was reported [29].…”
Section: Discussionmentioning
confidence: 88%
“…A growing body of evidence has reported that the onset rate and mortality rate from major cardiovascular diseases is influenced by seasonal variation and APE is of no exception ( 3 5 ). Several studies demonstrated a peak incidence and mortality rate of APE during winter season, conflicting results on the influence of weather on disease outcomes have been presented in literature ( 3 , 4 , 6 , 7 ). However, all published studies were epidemiology investigations, and systemic clinical and hemodynamic features of APE were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated, there could be a connection between cold weather and morbidity as well as mortality rate of APE, though specific pathophysiological mechanisms are still under investigation ( 8 11 ). Several factors may potentially contribute to cold weather effect on the adverse clinical outcome of APE such as abnormal coagulation system, peripheral vasoconstriction, reduced activity, combined cardiovascular disease, et al, which favors prothrombotic changes, cardiac dysfunction and hemodynamic collapse ( 6 , 12 , 13 ). However, previous studies failed to comprehensively investigate the cardiac function and hemodynamic status of APE patients and their values in predicting clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%